ABDOME AGUDO OBSTRUTIVO POR DIVERTÍCULO DE MECKEL EM ADULTO - Oliveira, Stéphanie Gonçalves; Machado, Bárbara Chaves Lopes; Cuellar, Pedro Manuel Gonzalez Cuella; Dias, Fellipe Camargo Ferreira; Guedes, Virgílio Ribeiro (Revista de Patologia do Tocantins, 2018)
O Divertículo de Meckel é a anomalia congênita mais encontrada no intestino delgado. A alteração é causada pela obliteração incompleta do ducto onfalomesentérico. Geralmente a doença diverticular é assintomática e a probabilidade de manifestar sintomas, como obstrução intestinal, diminui com a idade. Embora à maioria permaneça em silêncio, é importante sempre considerar o divertículo de Meckel como um diagnóstico diferencial em todos os pacientes que apresentem abdome agudo para evitar morbidade e mortalidade associada a complicações tardias. Palavras-chave: divertículo de Meckel; obstrução intestinal; abdome agudo obstrutivo. ABSTRACT The Meckel Diverticulum is the most common congenital anomaly found in the small intestine. The change is caused by incomplete obliteration of the omphalomesenteric duct. Diverticular disease is usually asymptomatic and the likelihood of manifesting symptoms, such as bowel obstruction, decreases with age. Although most remain silent, it is important to always consider Meckel's diverticulum as a differential diagnosis in all patients with acute abdomen to avoid morbidity and mortality associated with late complications. The following report is about a rare case of obstructive acute abdome in adult patients caused by the presence of a meckel diverticulo. Keywords: meckel diverticulum; intestinal obstruction; obstructive acute abdomen.